On the linkage between mesospheric gravity waves and occurrence of equatorial plasma bubble observed during the low solar activity - Taori, A.; Kamalakar, V.; Joshi, L.M.; Sripathi, S.; Patra, A. K. (My University, 2012)
In this paper, the linkage between the low-latitude mesospheric gravity waves and the equatorial plasma bubble (EPB) have been investigated using simultaneously Rayleigh lidar and VHF radar observations from Gadanki (13.5oN, 79.2oE) and ionosonde observations from Tirunelveli (8.7oN, 77.8oE) made between 2007 and 2009 when solar activity was undergoing a deep minima. The two sets of observations have been analysed, each comprising of one case having EPB and another without EPB observed on two nearby nights. Observations show that the occurrences of plume structures in the radar observations are found to have a close link with the amplitudes of the short period gravity waves in the mesospheric temperature. It is argued that such waves have an important role in seeding the Rayleigh-Taylor (RT) instability manifesting EPB.
Keywords: Equatorial plasma bubble (EPB); Equatorial spread F (ESF); Mesospheric gravity wave; Rayleigh-Taylor (RT) instability